Analysis of Teledentistry in Management Dentist’s Practice against the Health RUU “Omnibus Law” With the Legal Digitalization Aspects - Br.Sembiring, Tamaulina; Auliya, Viona shafa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Despite its potential, teledentistry faces legal complexities related to patient privacy, data security, and compliance with existing health laws. The study employs a normative juridical approach, reviewing relevant legal frameworks such as the Health Omnibus Law, ITE Law, and specific ministerial decrees governing telemedicine. Discussions highlight the rights and responsibilities of dental practitioners and patients in the digital health landscape, emphasizing the need for stringent data protection measures and professional accountability. Key findings underscore the necessity for tailored regulations that comprehensively address teledentistry's operational standards and legal safeguards. While existing laws provide a foundation, gaps remain concerning specific guidelines for teledentistry practices. Recommendations include the establishment of precise legal frameworks that ensure patient confidentiality, promote technological innovation, and mitigate legal risks associated with online healthcare services.This research contributes to the ongoing discourse on integrating digital technologies in healthcare delivery, advocating for regulatory clarity to foster trust and efficiency in teledentistry services in Indonesia.